The Influence of Green Accounting and Good Corporate Governance Mechanisms on the Financial Performance of Energy Sector Companies Listed on the Indonesia Stock Exchange for the Period 2021-2023 - Sianturi, Riyan Andika; Sagala, Lamria; Simanjuntak, Wesly Andri; Ginting, Mitha Christina (Future Science, 2025)
This study examines the influence of Green Accounting and the Good Corporate Governance Mechanism on Financial Performance in energy sector companies listed on the Indonesia Stock Exchange during the 2021-2023 period. The population used was 90 companies, and the sample was 17 companies and the multiple linear regression analysis method was used through SPSS 26. The results of the analysis show that partially, Green Accounting has a positive but not significant effect on the company's financial performance. Meanwhile, Good Corporate Governance partially shows a significant positive influence on financial performance. When tested simultaneously, these two variables (Green Accounting and Good Corporate Governance) were proven to have a significant effect on the financial performance of energy sector companies. From the results of the determination coefficient test (R Square), it was found that the variables Green Accounting and Good Corporate Governance were only able to explain the variation in financial performance by 13.6%. This figure shows a relatively small contribution, while most (86.4%) of the variation in financial performance is influenced by other variables not included in the regression model of this study. These findings indicate that although the implementation of Good Corporate Governance has a significant positive impact, the implementation of Green Accounting has not had a significant impact on the financial performance of energy companies in Indonesia. This raises questions about the effectiveness of Green Accounting practices in the context of the energy industry in Indonesia or the possibility of other moderation factors that need to be considered in future research such as increasing the number of observation periods, using a wider range of research objects and adding other variables that affect financial performance.